Thermo-oxidative degradation of chitin and chitosan derived from dead bees - Abdurazakov Mukhitdin; Akhimbetova Gulnara; Turaev Jamoliddin; Atakhanov Abdumutolib; Rashidova Sayyora (EPJ Web of Conferences)
This study investigates the thermo-oxidative degradation of chitin and chitosan extracted from dead bees using thermal analysis methods. The research reveals both similarities and unique characteristics in the thermal decomposition of these polysaccharides, along with a comparative assessment of their thermal stability. Utilizing thermogravimetry, derivative thermogravimetry, and differential scanning calorimetry techniques, the study identifies three distinct stages of thermal decomposition for both biopolymers: water desorption, active pyrolysis, and final decomposition with residual carbon formation. The findings demonstrate that chitin exhibits higher thermal stability compared to chitosan, likely due to its acetylated structure. Chitin undergoes desorption of both free and bound water molecules, while chitosan only loses free water. The study provides valuable insights into the thermal behavior of these biopolymers derived from dead bees, which is crucial for their application in various fields such as biomedicine, agriculture, and materials science. The use of dead bees as a raw material presents a cost-effective alternative to traditional sources like crustacean shells for producing chitin and chitosan.